ANALISIS SEISMOTEKTONIK UNTUK PENANGGULANGAN DAERAH RAWAN BENCANA GEMPA BUMI - Jayadi, Harsano; Soehaimi, Asdani (JFT : Jurnal Fisika dan Terapannya, 2016)
Tana Toraja located in the compression belt of two active fault seismic source zones. There are Palu- Koro and the Walanai faults have resulted the eastward, movement of the Banggai-Sula micro continent since neogen time. The field observations of the neotectonic holosen age were  found as the river deposit and beachsand terraces and the fault  fan structure where there  are consist of three teracces units  which the maximum high of  the oldest terrace (±100.000 years)  about of 12 m and the minimum about of  7 m. Base on the differences high of the maximum terrace  units in the Salu Sadang and Rongkong rivers, so  the maximum magnitude earthquake displacement (md) can be calculated at every fault segments. The evaluation of geological structures and earthquake data, this region can be devided  into four seismic source zones there are the salu sadang, The  Buttu Karoa-Lamasi Sabang  active faults, the old volcano tectonic earthquakes of the Buttu-Karoa-Kalumpang Mamuju and the volcano tectonic earthquakes of the Limbong Seismic Zource Zone. Base on tne neotectonic condition and the existing of seismic source zones above, Tana Toraja and surrounding area is one of the potential seismic hazard area in the South Sulawesi region which must be have more attention.